KAJIAN YURIDIS FUNGSI PENCEGAHAN KOMISI PEMBERANTASAN KORUPSI DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK DI PROVINSI DKI JAKARTA - Mahardika .; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2018)
In Indonesia, corruption is rampant in the procurement of goods and services. The institution authorized to deal with corruption is the Corruption Eradication Commission (KPK). One of the tasks of the Corruption Eradication Commission is to carry out surveillance and preventive actions so that there are not many corruption cases that can harm the country but the prevention function has not been maximally implemented. Therefore, the author proposes the issue of how is the juridical study of Corruption Eradication Commission’s preventive function in eradicating corruption of the electronic procurement of goods and services in DKI Jakarta province? The author analizes the problem using normative research methods, with the technique of research legislation approaches. Corruption in the procurement of goods and services is very widespread because there are still gaps or weaknesses used to commit corruption. Existing weaknesses include regulation, principles in procurement of goods and services, supervision, and implementation of procurement of goods and services. Likewise, the implementation of KPK in terms of prevention is still lacking. The KPK should be an institution tasked with eradicating corruption. In addition to supervision, the KPK should prioritize implementing prevention so that corruption does not occur. The thing that can be done by KPK includes tightening supervision in the procurement of goods and services.